COMPLETE CHARACTERIZATION OF UNIVERSAL FLUCTUATIONS IN QUASI-ONE-DIMENSIONAL MESOSCOPIC CONDUCTORS - Chalker, J; Macedo, A (1993)
Mesoscopic fluctuations in the transport properties of quasi-one- dimensional conductors are studied via the eigenvalue distribution of the transmission matrix. Fluctuations in the universal regime are characterized completely by the two-point correlation function of the eigenvlaue density at scales large compared to the mean eigenvalue spacing. This correlation function is calculated exactly. © 1993 The American Physical Society.